Presumed Polymyositis in Chronic Hepatitis C: Navigating Diagnostic Uncertainty and Therapeutic Imperatives in Recurrent Myopathy - I Ketut Wardika; Pande Ketut Kurniari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Polymyositis (PM) is a cell-mediated inflammatory myopathy for which viral triggers, particularly the Hepatitis C virus (HCV), are increasingly recognized. The convergence of these conditions creates a formidable clinical scenario, often compelling urgent therapeutic intervention despite incomplete diagnostic data. This report explores the management of such a case, highlighting the pragmatic decision-making required when definitive investigations are deferred. Case presentation: A 48-year-old male with untreated chronic HCV infection (Genotype 1b, viral load 2.8 x 10⁶ IU/mL) presented with a debilitating relapse of severe, symmetric proximal muscle weakness, three years after a similar episode. He exhibited profound weakness (Medical Research Council grade 2/5 in hip flexors) and marked myonecrosis (Creatine Kinase 8,572 U/L). Although comprehensive myositis-specific autoantibodies were negative, a strong clinical and biochemical profile led to a presumptive diagnosis of an acute PM exacerbation. Definitive diagnostics, including muscle biopsy, were deferred by the patient. Empirical treatment with high-dose corticosteroids and azathioprine was initiated, predicated on a careful risk-benefit analysis concerning immunosuppression in active viral infection. This strategy resulted in rapid and significant clinical and biochemical improvement. The patient was subsequently scheduled for direct-acting antiviral therapy to address the underlying viral trigger. Conclusion: This case underscores the critical challenge of managing severe, presumed autoimmune disease in the face of diagnostic ambiguity. It demonstrates that a therapeutic strategy guided by strong clinical evidence can be effective for controlling acute, disabling flares. Furthermore, it champions a necessary dual-paradigm approach: acute immunomodulation to preserve function, followed by targeted antiviral therapy to eradicate the probable etiological trigger, thereby aiming to prevent future recurrence and achieve durable remission.